Brief dispersion of a putative B.1.1.28-derived SARS-CoV-2 lineage harboring additional N234P and E471Q spike protein mutations in individuals crossing the Argentina-Brazil border. Issue 49 (September 2022) - Soares da Silva, Mariana; Gularte, Juliana Schons; Demoliner, Meriane; Hansen, Alana Witt; Heldt, Fágner Henrique; Filippi, Micheli; Luckmann, Cristiane Borba; Malayhka de Abreu Góes Pereira, Vyctoria; de Almeida Vaucher, Rodrigo; Barboza, Victor dos Santos; Giongo, Janice Luehring; Rosa, Raquel Borba; et al.
Abstract: Background: SARS-CoV-2, the virus that causes COVID-19, is constantly mutating, leading to new variants that culminate in a temporal lineages fluctuation. B.1.1.28 lineage has been evolving in Brazil since February 2020 and originated P.1 (VOC), P.2 (VOI) and other P.Xs proposed as new variants. Methods and results: In this study, through the Illumina platform, we performed the whole-genome sequencing of 26 positive samples of SARS-CoV-2. Employing variant calling analysis on FASTQ reads and phylogenetic inference, we report a brief dispersion of a potentially new B.1.1.28-derived variant detected between 2021 May and June in individuals crossing the border between Brazil and Argentina, and local spread to inpatients from hospitals at the Rio Grande do Sul state capital (Porto Alegre). Besides, the Rio Grande do Sul State SARS-CoV-2 genomic epidemiological data was analyzed and showed an important B.1.1.28 peak in RS at the same period (May–June), even in the presence of a major Gamma wave. Conclusions: The emergence of a putative B.1.1.28-derived lineage was identified in travelers crossing Brazil-Argentina border representing an important peak of B.1.1.28 in RS State with a decreased in Gamma variant frequency in the same period of time. Highlights: Emergence of putative B.1.1.28-derided lineage in individuals crossing the Brazil-Argentina border. Newly additional non-synonymous mutations identified. Presence of a B.1.1.28 lineage important peak in RS State concomitant with the cases reported herein.